Helicobacter pylori induces transendothelial migration of activated memory T cells - Enarsson, Karin; Brisslert, Mikael; Backert, Steffen; Quiding-Järbrink, Marianne (Infection and Immunity, 2005)
Helicobacter pylori infection is associated with pronounced infiltration of granulocytes and lymphocytes into the gastric mucosa, resulting in active chronic gastritis that may develop into duodenal ulcer disease or gastric adenocarcinoma. Infiltrating T cells play a major role in the pathology of these diseases, but the signals involved in recruitment of T cells from blood to H. pylori-infected tissues are not well understood. We therefore examined H. pylori-induced T-cell transendothelial migration (TEM). The Transwell system, employing a monolayer of human umbilical vein endothelial cells, was used as a model to study TEM. H. pylori induced a significant T-cell migration, compared to spontaneous migration. CD4+ and CD8+ T cells migrated to the same extent in response to H. pylori, whereas there was significantly larger transmigration of memory T cells compared to naive T cells. Both H. pylori culture filtrate and urease induced migration, and the presence of the H. pylori cag pathogenicity island increased TEM. T-cell TEM was mediated by LFA-1-ICAM-1 interactions in accordance with an increased ICAM-1 expression on the endothelial cells after contact with H. pylori. Migrating T cells had increased expression of activation marker CD69 and chemokine receptors CXCR3, CCR4, and CCR9. Furthermore, T cells migrating in response to H. pylori secreted Th1 but not Th2 cytokines upon stimulation. In conclusion, our data indicate that live H. pylori and its secreted products contribute to T-cell recruitment to the gastric mucosa and that the responding T cells have an activated memory Th1 phenotype.
Created from Fastlane, Scopus look-up